Investigation of the effects of magnesium orotate in a model of primary generalized seizures - A. G. Kalacheva; O. A. Gromova; T. R. Grishina; T. E. Bogacheva; V. I. Demidov; I. Yu. Torshin; I. K. Tomilova (Неврология, нейропсихиатрия, психосоматика, 2017)
Objective: to investigate the anticonvulsant and neuroprotective effects of magnesium orotate in a rat thiosemicarbazide model of seizures in rats.Material and methods. The investigation was conducted in 112 male albino rats weighing 200 g, in which severe clonic-tonic seizures weresimulated by the convulsant thiosemicarbazide. The anticonvulsant effects against of thiosemicarbazide-induced seizures were evaluated in the following drugs: gabapentin; a combination of gabapentin + magnesium orotate; sodium valproate; a combination of sodium valproate + magnesium orotate; and magnesium orotate. The neurological status, characteristics of seizures, survival rates, body weight, and plasma and red blood cell magnesium concentrations were compared. After completing the animal experiment, the animals were euthanized and the histological characteristics of their brains and nerves were analyzed.Results. Magnesium orotate was ascertained to reduce the severity and duration of thiosemicarbazide-induced seizures, to increase animal survival rates, and to potentiate the anticonvulsant action of gabapentin and sodium valproate. The neurohistological findings showed that the used model of seizures led to ischemic brain damage.Conclusion. It has been concluded that magnesium orotate minimized the level of ischemic damage to nerve cells and contributed to restoration of the morphology of brain tissues after thiosemicarbazide administration.